Sleep Quality and Factors Related to Sleep and Self-esteem in the Elderly - Choombuathong, Anchalee; Chalopatham, Wijit; Dhongyooyen, Pichaya; Chokchaiworrarat, Sarayuth; Thamwattana, Kantapol; Changsap, Bangon; Suksawang, Poonpong (Journal of Health Science of Thailand, 2017)
The purpose of this study was to study the sleep quality, disturbing factors and self-esteem among the elderly. The research subjects consisted of 72 persons from Banglamung nursing home in Chonburi Province during June to August 2013 recruited through a purposive sampling. Data were collected by individual interview. The research instruments used were (1) a form of Sleep Quality Assessment which was a translated and modified from Pittsburgh Sleep Quality Index (PSQI), (2) a form to assess factors influencing sleep and (3) Rosenberg’s self-esteem scale. Data were analyzed using descriptive statistics in percentage, mean, standard deviation, Pearson’s product moment correlation coefficient and stepwise multiple regression analysis. It was found that 42.86% of subjects had a good sleep quality and the remaining of them had a poor quality. Gender and age did not affect the quality of sleep. Factors significantly disturbing and predicting the sleep quality were pain and senility (p<0.001). These 2 predictors accounted for 23.7% of the variance. The subjects’ self-esteem mean score was 29.87±4.15, which was relatively high. Gender, age and education were not found to affect self-esteem. These findings provide preliminary information for health care plan in order to promote sleep quality, manage sleep disturbance and promote higher self-esteem score in the elderly.